Peran Penyuluh Pertanian dalam Penerapan Pembuatan Pupuk Organik dari Rumen Sapi di Kabupaten Gresik - Sukmajati, Arga; Djazuli, Raden Achmad; Agustina, Rohmatin (Jurusan Agribisnis, Fakultas Pertanian, Universitas Siliwangi, 2025)
This study examines the role of agricultural extension workers in implementing organic fertilizer production technology from cattle rumen in Gresik Regency. It aims to analyze farmers' perceptions of extension workers' performance and factors influencing the effectiveness of extension programs. The method used is a survey with purposive sampling of participating farmers. Results show farmers' positive perceptions of extension workers' role in transferring knowledge and skills. However, the frequency of field visits and post-training support needs improvement. Significant influencing factors include extension workers' competence, extension methods, and farmers' socio-economic characteristics. The study recommends enhancing extension workers' capacity and adapting extension methods. Optimizing the role of extension workers as change agents is crucial to promote sustainable agricultural technology adoption, increase productivity, and preserve the environment through livestock waste utilization